Train day! : with four phonics stories - Rae, Elspeth, 1973-; Rae, Rowena (Rae, Elspeth, 1973- Meg and Greg, 2025)
"In the sixth book in the phonics-based, decodable Meg and Greg series, Meg and Greg are on vacation, in four stories that introduce readers to long vowels. Includes illustrations and worksheets."--